2011
DOI: 10.1007/s00262-011-1029-z
|View full text |Cite
|
Sign up to set email alerts
|

Distinct myeloid suppressor cell subsets correlate with plasma IL-6 and IL-10 and reduced interferon-alpha signaling in CD4+ T cells from patients with GI malignancy

Abstract: Interferon-alpha (IFN-α) promotes anti-tumor immunity through its actions on immune cells. We hypothesized that elevated percentages of myeloid-derived suppressor cells (MDSC) and increased pro-inflammatory cytokines in peripheral blood would be associated with impaired response to IFN-α in patients with gastrointestinal (GI) malignancies. This study evaluated relationships between plasma IL-6, IL-10, circulating MDSC subsets, and IFN-α-induced signal transduction in 40 patients with GI malignancies. Plasma IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 52 publications
5
119
1
Order By: Relevance
“…The systemic increase of IL-6 levels in the plasma of patients with cancer (28,29) markedly correlated with proportional accumulation of MDSC (30,31). These reports support our findings and previous reports (39,40) that MDSC produce IL-6 in tumor-bearing mice.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The systemic increase of IL-6 levels in the plasma of patients with cancer (28,29) markedly correlated with proportional accumulation of MDSC (30,31). These reports support our findings and previous reports (39,40) that MDSC produce IL-6 in tumor-bearing mice.…”
Section: Discussionsupporting
confidence: 82%
“…Chronic inflammation and increased levels of inflammatory cytokines including IL-6 have been reported in patients with various type of tumors (26), and an elevated level of IL-6 fostering progressive expansion of tumor cells (27) has been associated with poor clinical outcome (28)(29)(30)(31). Here, we focused on the association between the functional impairment of CD4 þ T cells and immune-suppressive effects of the tumor-induced inflammation-related factors, IL-6 and MDSC.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to murine MDSCs, which are defined by the expression of Gr-1 and CD11b, the corresponding cells in humans are inadequately characterized due to the lack of uniform markers. MDSCs have been intensively studied in cancer and were found to have important implications in disease progression (38)(39)(40). To investigate the MDSCs, we chose 2 subsets of markers that have shown statistical association with human cancer disease stages (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IL-6 levels have been found to correlate with increased MDSC frequencies and suppressive functions in tumor-bearing hosts [48,78]. It has been shown that IL-6 mediated the generation, migration and activation of MDSCs via transcription factor STAT3 [26,33,79].…”
Section: General Characteristic Of Mdscsmentioning
confidence: 99%